Epistaxis in Chiang Mai University Hospital - Saisaward Chaiyasate (2018)
Objectives: Epistaxis is a common otolaryngologic emergency, and can be severe or even fatal. The causes can be from local or systemic illnesses. The aim of this study was to review and analyze the general and specific data causes, management and results of epistaxis in patients admitted in Chiang Mai University Hospital. Material and Method: A retrospective study by reviewing charts of new epistaxis inpatients, admitted to Chiang Mai University Hospital between January 2001 and July 2004, was done. Results: From 55 cases reviewed, 41 were males (74.5%) and 14 females (25.5%). The mean age was 46.98 ± 17 years (12-87 years). The peak of prevalence was between January and April. The average length of hospital stay was 6.2 ± 3.8 days, (1-17 days). The most common cause of epistaxis was hypertension (32.72%) followed by tumor, local trauma and coagulopathy, subsequently. About 18 per cent of the patients had more than one cause of the illness. According to the bleeding site, 33 patients (60%) had anterior bleeding, 14 (25.45%) had posterior bleeding, and the rest had non-identifiable bleeding sites. There were 5 abnormalities from 52 patients (9.6%) tested for clotting profile. About one third of the patients received more than one type of procedure, while 2 patients (3.6%) treated by a local hospital before being transfered, were observed with successful outcome. Conclusion: The most common and preventable causes of epistaxis in this review are hypertension and facial and paranasal sinus injuries. The other common curable cause is tumor. Otolaryngologists and general physicians should find out the causes and know characteristics of the patients and diseases, especially in their own area of practice in order to be able to perform optimal management.